Determinants of Tuberculosis Infection among Adult HIV Positives Attending Clinical Care in Western Ethiopia: A Case-Control Study - Hatoluf Melkamu; Berhanu Seyoum; Yadeta Dessie (AIDS Research and Treatment)
There has been a drastic rise of tuberculosis (TB) infection across the world associated with the pandemic occurrence of HIV/AIDS. There are various determinants factors that increase the chance of TB infection among HIV positives (TB/HIV confection) that varies contextually. This study aimed to assess the determinants of TB/HIV coinfection among adult HIV positives attending clinical care at two public health facilities in Nekemte, western Ethiopia. Unmatched case-control study was conducted from December 26, 2011, to February 29, 2012. Cases were 123 TB infected HIV positives, and controls were 246 non-TB infected HIV positives. Being divorced/widowed , 95% CI (1.70, 7.88), not attending formal education , 95% CI (2.20, 14.15), being underweight ( kg/m2) , 95% CI (2.18, 6.87), having history of diabetic mellitus , 95% CI (1.33, 9.94), and being in advanced WHO HIV/AIDS clinical staging , 95% CI (1.32, 3.98), were determinant factors associated with TB/HIV co-infection. Having a separate kitchen , 95% CI (0.28, 0.81) showed protective role. For most of these determinants interventions can be made at individual and institutional levels, whereas, factors like education and nutrition need societal level integrations.